(untitled) (Indian Journal of Arid Horticulture, 2017)
An experiment was carried out at S.K.N.A.U.,Jobner (Jaipur) Rajasthan to find out the comparative effect of organic manures and inorganic fertilizers on growth parameters of three years old ber orchard cv. Gola. Four levels of organic manures (control, FYM @ 20 kg/plant, Vermi- compost @ 6 kg/plant and poultry manure @ 8 kg/plant) and five levels of RDF (control, 50% RDF, 75% RDF, 100% RDF and 125% RDF) in Randomized Block Design with three replications were taken to provide balance fertilization of ber under semi-arid region of northern India during 2015-16. The experimental results revealed that application of Vermi-compost @ 6 kg/plant and 125% recommended dose of fertilizers significantly influence the growth parameters (Plant height, plant spread (E-W and N-S), number of primary branches, average length of primary branch, number of secondary branches per primary branch and leaf area), fruit yield (kg/plant and q/ha) and fruit quality (TSS and acidity content) of experimental plants